If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = (2m + 7) Reorder the terms: 6 = (7 + 2m) Remove parenthesis around (7 + 2m) 6 = 7 + 2m Solving 6 = 7 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 6 + -2m = 7 + 2m + -2m Combine like terms: 2m + -2m = 0 6 + -2m = 7 + 0 6 + -2m = 7 Add '-6' to each side of the equation. 6 + -6 + -2m = 7 + -6 Combine like terms: 6 + -6 = 0 0 + -2m = 7 + -6 -2m = 7 + -6 Combine like terms: 7 + -6 = 1 -2m = 1 Divide each side by '-2'. m = -0.5 Simplifying m = -0.5
| 4k-2=2k+4 | | 240.00+x(0.25)=405.00 | | 2(0.3x+4)-1=1.33x-3+x | | 25+(5x)=50+(10x) | | 10pq+8p= | | -3h-4=h-8 | | 4=(m+13) | | 81-x=93-2x | | 5+-11t=7(5+-2t) | | 8x^2+7x-4=0 | | 7g(-3h+1)= | | 81-x=93-x | | 2a+2=a+4 | | 79-(101-5y)=2(101-5y)+y | | 6.5(x-4)=-0.5x+30 | | 5=(x+8) | | -5x+6y=30 | | 19x=12x | | 11x+2=5x+10+58 | | -5-x=1+2x | | 4d=7-7 | | 8x+2+70+60= | | -5(a-6)+2a=9 | | (3x-6y-1)+(-x+y+10)= | | 3w+10=-3+8w-9w | | 4(2y+1)-2y=-26 | | 1/3(102-12c)=5(3c+10) | | 5x-x-3=2x+6 | | M-3=7m-21 | | 4n-(7-6n)=13 | | 6x+3=3(2x+3) | | 2x-11=23 |